Influence of Plio-Pleistocene basin hydrology on the Turkana hominin enamel carbonate δ18O values. Issue 86 (September 2015) - Quinn, Rhonda L.
Abstract: Stable oxygen isotopes of hominin enamel carbonate (δ 18 OEC ) provide a window into aspects of past drinking behavior and diet, body size, breastfeeding and weaning, mobility, and paleoclimate. It is tempting to compare all hominins across time and space in order to gauge species-level adaptations to changing environments and niche separation between those living sympatrically. Basinal, sub-basinal, and micro-environmental differences, however, may exert an influence on variation in enamel carbonate isotopic values that must be reconciled before hominin species across Africa can be meaningfully compared. Plio-Pleistocene Turkana hominin δ 18 OEC values show a considerable spread, potentially revealing many intrinsic and extrinsic contributing factors operating on different scales. In this study, I examine Turkana hominin δ 18 OEC values relative to identity (taxon, tooth type and number, body size of taxon), dietary (δ 13 C value, Turkana coeval and modern mammalian δ 18 OEC values), and contextual (time, depositional environment) information of each specimen and collection locality and discuss various potential influences. Turkana hominin δ 18 OEC values may primarily reflect differences in imbibed water sources (lake vs. river) as a function of evolving basin hydrology.